Integrated physiological and transcriptomic analysis reveals the key pathways of Rosa rugosa in response to salt-alkali stress - Han, Lulu; Lu, Yan; Niu, Mengxin; Liu, Meiying; Yang, Kebin (Frontiers in Plant Science, 2025)
IntroductionAbiotic stressors, particularly saline–alkali stress, restrict plant growth and development. Rosa rugosa, which grows in coastal areas and exhibits high saline–alkali tolerance, serves as an ideal model for analyzing rose response mechanisms to saline–alkali stress (SAS). However, its response mechanisms have not yet been elucidated.MethodsThis study examined SAS using a 150 mmol·L−1 saline–alkali solution and analyzed the physiological and molecular response mechanisms using physiological and biochemical indicators and high-throughput RNA-sequencing technology.ResultsUnder SAS, reactive oxygen species accumulation increased, resulting in extensive oxidative damage to cell membranes. In response, the superoxide dismutase, peroxidase, and catalase activities, along with the contents of soluble sugars, soluble proteins, and proline increased. Furthermore, 325, 2,197, 4,266, and 6,842 differentially expressed genes (DEGs) were identified at 6, 12, 24, and 48 h of SAS, respectively. Functional annotation and pathway enrichment analyses indicated that DEGs were primarily involved in cell wall organization, enzyme activity, biosynthesis of secondary metabolites, and photosynthesis pathways. Several structural genes from the phenylpropanoid biosynthesis pathway, including PAL, 4CL, HCT, CCR, COMT, CHS, CHI, and DFR, were identified by qRT-PCR, which positively responded to SAS and peaked at 12 h. Weighted gene co-expression network analysis revealed that PKS likely functions as the hub gene in the secondary metabolic pathway responding to SAS.DiscussionThis study advances understanding of saline–alkali resistance mechanisms, and the identified genes and metabolic pathways can enhance future rose breeding efforts.